SYNTHESIS AND CHARACTERIZATION OF PEROXIDE SENSOR BASED ON PVA-PANI NANOCOMPOSITE - H G. WANKHADE; S. V. MANORAMA; G.N.CHAUDHARI (International Journal of Pharma and Bio Sciences, 2015)
Peroxidase has been immobilized onto the PVA-PANI nanocomposite film deposited onto gold plate via physical adsorption for peroxide detection. PVA-PANI nanocomposite was characterized by scanning electron micrograph (SEM) before and after immobilization. The SEM picture clearly shows the immobilization of peroxidase onto the PVA-PANI. The cyclic voltametric study is also carried out for the as prepared peroxidase immobilized nanobiocomposite, these graphs clearly shows the redox curve which confirms immobilization. Synthesized nanocomposite was characterized by XRD and impedance analysis. Experimental results indicate that the ac conductivity depend on temperature and frequency. From the XRD study the particle size for PANI was found to be 40 nm (approx).